Analysis of Lightning Protection for Ground-Mounted Photovoltaic Farm of Direct Lightning Current Size 5 kA 10 kA and 20 kA - อัศวฉัตรสกุล วิศรุต; ภูมิกิตติพิชญ์ กฤษณ์ชนม์ (RMUTL Engineering Journal, 2019)
This article analyzes the impact of maximum voltage and maximum current ​​in the event of a lightning incident in the solar power generation system installed on the ground not more than 10 MW. With the installation protection devices for 1 phase and 3 phase. The simulating the direct lightning at waveform, 10/350 ms, which the lightning current in 3 levels is 5 kA, 10 kA and 20 kA, which is not more than the lightning current value of Thailand. By using the PSCAD version 4.6 program to create a model and analyze the results from the waveform graph for maximum voltage and maximum current, which defines the DC side points of the solar cells to the inverter and Point 2 on the DC and AC. The results of the comparison of the maximum voltage level after the design of the lightning protection device is installed. In the case of direct lightning, the DC side has a voltage drop in the DC system equal to 0.77 kV 0.55 kV and 0.12 kV, respectively. The voltage in the AC system is reduced to 0.41 kV in the case of direct lightning on the AC side with the voltage in the system. DC has a constant value of 0.96 kV and the voltage in the AC system is reduced by -2.40 kV -4.50 kV -8.66 kV, respectively. The design and analysis of results can be used as a guideline for the lightning protection system in solar power generation located on the ground.